The Use of Puzzle 3D Puzzle in Therapy Media Fine Motor Skill to Autis Syndrom at Talenta’s Therapy Semarang - Hania, Dian Andari; Windiarti, Rina (Universitas Negeri Semarang, 2016)
This research attempts to look using of the puzzle 3D puzzle in media therapy to autis syndrom for development of the fine motor in Talenta’s therapy Semarang. This research in a qualitative methode with the data collection with the observation, interviews and documentation. The analysys research has been concluded that the children autis affect generation of kids able to puzzle 3D puzzle. The insensity of the time it takes is long as children can’t coordinate eyes and hand well. With the media puzzle 3D puzzle could be used to lessen the activity been often held by the autis, as hit, clawing, vlaping, etc. A role that puzzle 3D puzzle this as a media play therapy can be given to the autis in any therapy program to give stimulate fine motor skill autis for child development.